2020
DOI: 10.5125/jkaoms.2020.46.5.328
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a difficulty index for mandibular third molars with extraction time

Abstract: Objectives This study aimed to validate the effectiveness of a recently proposed difficulty index for removal of impacted mandibular third molars based on extraction time and suggest a modified difficulty index including the presence of pathologic conditions associated with third molars. Materials and Methods This retrospective study enrolled 65 male patients younger than 25 years with third molars. Extraction time was calculated from start of the incision to the last s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…The inclusion criteria of the patients were as follows: (1) healthy status without any underlying disease, (2) impacted mandibular third molar which is horizontal (80 to 100°) with less than half of the third molar crown above the CEJ of the adjacent second molar and contacted with the inferior mandibular canal on computed tomography (Fig. 1 ) [ 8 , 9 ], and (3) facial MRI within 48 h after surgical extraction of their mandibular third molar. The exclusion criteria were as follows: (1) simultaneous extraction of impacted maxillary third molar with incision, ostectomy, or odontomy, (2) poor oral hygiene control, and (3) uncontrolled systemic diseases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion criteria of the patients were as follows: (1) healthy status without any underlying disease, (2) impacted mandibular third molar which is horizontal (80 to 100°) with less than half of the third molar crown above the CEJ of the adjacent second molar and contacted with the inferior mandibular canal on computed tomography (Fig. 1 ) [ 8 , 9 ], and (3) facial MRI within 48 h after surgical extraction of their mandibular third molar. The exclusion criteria were as follows: (1) simultaneous extraction of impacted maxillary third molar with incision, ostectomy, or odontomy, (2) poor oral hygiene control, and (3) uncontrolled systemic diseases.…”
Section: Methodsmentioning
confidence: 99%
“…
Fig. 1 Assessment of the impacted third molar position in computed tomography according to a previous study [ 8 ]. The spatial relationship was classified based on the angle measured between the long axis of the impacted third molar and the adjacent second molar (yellow lines and an asterisk mark).
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification of impaction status for M3M is mainly based on local anatomy and radiographs (11). Several classification systems have been proposed for evaluating the difficulty index for impacted M3M (12,13). All these classifications illustrate the relationship between radiological anatomy and surgical difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, operation time has also been shown to be a predictor of postoperative symptoms and is used as a proxy measure for extraction difficulty (7,16). Recent research has shown that the relationship between the M3M position, operation time, and surgical difficulty may be influenced by radiological factors such as the P-G level classification (12). These findings suggest a possible association between operation time and PoSS.…”
Section: Introductionmentioning
confidence: 99%